Fostering creativity and work engagement through perceived organizational support: the interactive role of stressors - Inam, Aneeq; Ho, Jo Ann; Zafar, Hina; Khan, Unaiza; Ahmed Sheikh, Adnan; Najam, Usama (Sage Publications, 2021)
The increasing interest of organizations in innovating and surviving during stressful work environments has led scholars to ponder ways to increase employee’s creativity. The study aims to empirically examine the relationship between perceived organizational support (POS) and employee creativity through work engagement and the moderating effect of challenge and hindrance stressors. The theoretical lens of social exchange theory was used to explain the study framework. Data was collected from 324 marketing personnel of the beverage and telecom sector in Pakistan and analyzed using structural equation modeling (SEM) with AMOS. The findings revealed that the direct relationship between POS with work engagement and employee creativity and work engagement with employee creativity was significant. Interestingly, the moderator has shown a prominent effect, which illustrated that low hindrance stressors strengthened the relationship between POS and work engagement. The study contributes by enhancing the employee’s creativity by reducing stressful working environments in many ways.